2021
DOI: 10.32819/021002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Recreational Transformation of the Grass Cover of Public Green Spaces

Abstract: The paper reveals regularities of grass projective cover variation depending on the level of recreational transformation of public green spaces, taking into account stand density and soil electrical conductivity. The hypothesis that herbaceous cover is positively influenced by moisture and trophicity of edaphotopes and the stand is an antagonist of herbaceous cover is confirmed. The nature of intra-ecosystem relationships of the park stand is influenced by the level of recreation. Assessment of the level of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…However, disturbance is also known to increase the invasibility of communities. Disturbance therefore poses an important problem for conservation management (Hobbs & Huenneke, 1992;Tkalich et al, 2021;Yorkina et al, 2021). Our study confirmed that up to 90% of the mapped sites represent significantly disturbed habitats with a high degree of anthropogenic influence.…”
Section: Discussionsupporting
confidence: 77%
“…However, disturbance is also known to increase the invasibility of communities. Disturbance therefore poses an important problem for conservation management (Hobbs & Huenneke, 1992;Tkalich et al, 2021;Yorkina et al, 2021). Our study confirmed that up to 90% of the mapped sites represent significantly disturbed habitats with a high degree of anthropogenic influence.…”
Section: Discussionsupporting
confidence: 77%
“…Water bodies can become disconnected and some of the floodplain water bodies are temporarily or permanently isolated (Kunakh et al, 2020(Kunakh et al, , 2021Teluk et al, 2020;Yorkina et al, 2021). After disconnection from neighbouring bodies of water, the water in the lake becomes slow-flowing or completely standing, resulting in the increased deposition of fine soil particles and an increase in the amount of silt and clay in the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement results of the device are presented in units of soil salt concentration (g/L). The comparison of HI 76305 measurements with laboratory data allowed us to estimate the unit conversion factor as 1 dS/m = 155 mg/L (Pennisi & van Iersel, 2002;Yorkina et al, 2021). The tree height was measured with an optical altimeter SUUNTO "PM-5/1520" (Finland).…”
Section: Methodsmentioning
confidence: 99%